1992
DOI: 10.1038/358080a0
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of a gene encoding a p53-associated protein in human sarcomas

Abstract: Despite extensive data linking mutations in the p53 gene to human tumorigenesis, little is known about the cellular regulators and mediators of p53 function. MDM2 is a strong candidate for one such cellular protein; the MDM2 gene was originally identified by virtue of its amplification in a spontaneously transformed derivative of mouse BALB/c cells and the MDM2 protein subsequently shown to bind to p53 in rat cells transfected with p53 genes. To determine whether MDM2 plays a role in human cancer, we have clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
1,300
5
21

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,821 publications
(1,353 citation statements)
references
References 25 publications
25
1,300
5
21
Order By: Relevance
“…), or with the cellular protein MDM-2. This protein has been identi®ed as the product of mdm-2 oncogene, which is ampli®ed in some types of tumour Oliner et al, 1992). This is an alternative mechanism of p53 inactivation which is common in many tumour types (including soft tissue sarcomas, neural tumours, bladder, cervical and breast carcinomas as well as leukaemias).…”
Section: From Oncogene To Tumour Suppressor Genementioning
confidence: 99%
See 1 more Smart Citation
“…), or with the cellular protein MDM-2. This protein has been identi®ed as the product of mdm-2 oncogene, which is ampli®ed in some types of tumour Oliner et al, 1992). This is an alternative mechanism of p53 inactivation which is common in many tumour types (including soft tissue sarcomas, neural tumours, bladder, cervical and breast carcinomas as well as leukaemias).…”
Section: From Oncogene To Tumour Suppressor Genementioning
confidence: 99%
“…For instance the product of the mdm2 oncogene, which binds and is believed to mask the activation domain of p53, is overexpressed in certain tumours, resulting in the abrogation of p53 function, accompanied by the proteolytic degradation of p53, mediated by the ubiquitin pathway Oliner et al, 1992Oliner et al, , 1993Midgley and Lane, 1997). Additional data showed that p53 may down-regulate the expression from a number of other promoters including those of the c-fos, c-jun, c-myc, b-actin, hsc-70, IL-6 genes (Ginsberg et al, 1991;Lechner et al, 1992;Ko and Prives, 1996).…”
Section: P53 a Sequence Speci®c Transactivatormentioning
confidence: 99%
“…Overexpression of the mdm2 gene in BALB/c 3T3 cells confers tumorigenicity in nude mice (Fakharzadeh et al, 1991). Later also the corresponding human mdm2 gene was identi®ed (Oliner et al, 1992). The mdm2 gene encodes a 490 amino acid protein which binds to the p53 protein and is thought to function as a regulator of p53.…”
Section: Introductionmentioning
confidence: 99%
“…The mdm2 gene encodes a 490 amino acid protein which binds to the p53 protein and is thought to function as a regulator of p53. The MDM2 protein binds to a region in the N-terminus of p53 representing the transcription activation domain of p53 Oliner et al, 1992). Overexpression of MDM2 protein inhibits both the transcriptional activation and the repression activities of p53 (Chen et al, 1995;Momand et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, MDM2 is amplified and overexpressed in several types of human malignancy, including sarcomas, breast carcinomas and brain tumors (Oliner et al, 1992;Momand et al, 1998). MDM2 is regulated by negative regulators including ADP-ribosylation factor, promyelocytic leukemia and ribosomal proteins L5, L11, L23, but positively regulated by Gankyrin, YY1 and kinase associated phosphatase 1 (reviewed in Lee and Lozano, 2006).…”
Section: Introductionmentioning
confidence: 99%